2004
DOI: 10.5713/ajas.2004.116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stocking Density and Transportation Time of Market Pigs on Their Behaviour, Plasma Concentrations of Glucose and Stress-associated Enzymes and Carcass Quality

Abstract: It is known that the transportation stress of market pigs can affect their carcass quality and that blood concentrations of glucose, creatine kinase (CK) and lactate dehydrogenase (LDH) are indicators of the transportation stress. Fifty-seven gilts and 57 barrows weighing approximately 110 kg were randomly assigned into six groups in a 3 [high (0.31 m 2 /100 kg BW)-, medium (0.35 m 2 )and low (0.39 m 2 )-stocking densities]×2 [1 h vs. 3 h transportation time] arrangement of treatments. Blood samples were taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0
2

Year Published

2009
2009
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 15 publications
2
31
0
2
Order By: Relevance
“…Sanz et al (1996) in young bull and Gregory (1998) for all species reported that in short journeys animals can have less time to adapt to the new situation than longer ones, obtaining higher stress response. In pigs, LDH increased after loading and declined in lairage until to achieve resting level (Kim et al, 2004;Averos et al, 2007). Nevertheless, while Kim et al (2004) observed that LDH was greater in pigs transported 3 h than those transported only for 1 h, Averos et al (2007) did not find differences due to transport duration comparing 1 h transport with 13 h. CK is released into the blood in response to muscle damage, e.g., bruising, and during vigorous exercise .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Sanz et al (1996) in young bull and Gregory (1998) for all species reported that in short journeys animals can have less time to adapt to the new situation than longer ones, obtaining higher stress response. In pigs, LDH increased after loading and declined in lairage until to achieve resting level (Kim et al, 2004;Averos et al, 2007). Nevertheless, while Kim et al (2004) observed that LDH was greater in pigs transported 3 h than those transported only for 1 h, Averos et al (2007) did not find differences due to transport duration comparing 1 h transport with 13 h. CK is released into the blood in response to muscle damage, e.g., bruising, and during vigorous exercise .…”
Section: Discussionmentioning
confidence: 79%
“…In pigs, LDH increased after loading and declined in lairage until to achieve resting level (Kim et al, 2004;Averos et al, 2007). Nevertheless, while Kim et al (2004) observed that LDH was greater in pigs transported 3 h than those transported only for 1 h, Averos et al (2007) did not find differences due to transport duration comparing 1 h transport with 13 h. CK is released into the blood in response to muscle damage, e.g., bruising, and during vigorous exercise . In our study, CK was similar between transport times, suggesting that minimal muscle trauma had occurred during transport and handling and that the experiment was carried out in good conditions.…”
Section: Discussionmentioning
confidence: 79%
“…Lambooy and Engel 1991;Guise et al 1998;Warriss 1998a;Kim et al 2004;Ritter et al 2007). Current legislation valid in EU countries since the 5 th of January 2007 requires all transported pig to have enough space to be able to lie down and stand up in their natural position.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we monitored the effect of the number of pigs transported in a vehicle (loading density was kept within the limits required by regulations). Even when complying with regulation requirements, the density of pigs in a vehicle can vary according to the number of transported pigs, it can however be optimised by choosing a vehicle of appropriate size, or by using transportable dividers, keeping in mind that both too low or too high density of animals has a negative influence on the welfare of transported pigs (Gade and Christensen 1998;Warriss 1998a;Kim et al 2004). Various numbers of pigs in one load are connected with different time requirements for loading, unloading and manipulation with pigs, i. e. with the time period when animals are exposed to an increased stress level connected with the transport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation